The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/eve.13649
|View full text |Cite
|
Sign up to set email alerts
|

Review of two viral agents of economic importance to the equine industry (equine herpesvirus‐1, and equine arteritis virus)

Abstract: Equine herpesvirus type-1 (EHV-1) and equine arteritis virus (EAV) are infectious agents that cause serious health risks to horse populations and are disbursed worldwide, which can lead to significant financial losses. In addition to being responsible for abortion and neonatal death, these viruses are associated with respiratory illness. Although previous research and reviews have been written on these viruses, both viruses still affect horse populations around the world and the vaccines currently available ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Equine arteritis virus is a member of the Alphaarterivirus genus within the Arteriviridae family (18). Although infections with this virus often remain subclinical, they can also lead to the development of clinical signs including pyrexia, depression, anorexia, oedema, conjunctivitis, petechial haemorrhages on mucosal surfaces and urticaria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equine arteritis virus is a member of the Alphaarterivirus genus within the Arteriviridae family (18). Although infections with this virus often remain subclinical, they can also lead to the development of clinical signs including pyrexia, depression, anorexia, oedema, conjunctivitis, petechial haemorrhages on mucosal surfaces and urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…Oedematous changes and degeneration of fibroblasts in the subvillous layers of the placenta could be observed as a result of infection (32). Between approximately 10% and over 50% of infected pregnant mares abort within 10 to 33 days of infection with the virus during the acute or early convalescent stages (6,16,18). In Poland, a longitudinal study performed between 1976 and 2010 showed that EAV infections were associated with over 23% of cases of abortion and neonatal death in the analysed period (5).…”
Section: Introductionmentioning
confidence: 99%